A new draft tube shape optimisation methodology of introducing inclined conical diffuser in hydraulic turbine. (15th February 2023) - Zhou, Xing; Wu, Hegao; Cheng, Li; Huang, Quanshui; Shi, Changzheng
Abstract: A grid-connected integrated system incorporating cascade hydropower, solar/photovoltaic, and wind power requires a hydraulic turbine to operate frequently under off-design conditions, resulting in a series of instability issues, such as pressure fluctuations. In this study, a new draft tube shape optimisation methodology of introducing an inclined conical diffuser for a Francis turbine was proposed to eliminate vortex rope and mitigate the associated pressure fluctuations. Four different inclination angles in the range of 0°–16.8° were considered to investigate the effectiveness of the modified draft tube. The results demonstrated that the maximum pressure fluctuation amplitude within the draft tube was 1.64% times the equivalent pressure under the rated water head for the modified draft tube, showing an 18.4% reduction compared with that of the traditional case. In addition, an overall index of P degree was proposed to quantitatively measure the mitigating impact of this type of modified draft tube on the pressure fluctuations. When the inclination angle is 16.8°, the P degree on the downstream and upstream sides decreases by 34.1% and 23.1%, respectively, when compared to the traditional draft tube. Based on a comprehensive comparison of the vortex rope, instantaneous axial velocity, and pressure distribution, the mitigating mechanism of the modified draft tube was further explored. Finally, further optimisation direction was pointed out by means of entropy production theory. Highlights: A new draft tube with inclined conical diffuser is proposed. Different inclination angles are investigated to alleviate flow instabilities. The maximum pressure fluctuation amplitude of modified draft tube is reduced by 18.4%. P degree is proposed to reflect the relative intensity of pressure fluctuation.